POPULATION STRUCTURE AND HABITATCHARACTERISTICS OF HARD CLAM (Meretrix meretrix)IN INTERTIDAL ZONE OF SUNGAI CINGAM VILLAGE OF RUPAT SUB DISTRICT OF BENGKALIS REGENCY - Kristoper Aritonang; Syafruddin Nasution; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTHard clam (M. meretrix) is bivalve that lives in the bottom of a water substrate that is a filter feeder. This research was conducted in July 2018 in the intertidal zone of Sungai Cingam Village, Rupat District. This research aims to knowhabitat characteristics, abundance, distribution patterns and size distribution of M. meretrix. The method used in this study was the survey method and determination of sampling location by purposive sampling. Measurements of water quality parameters weredone in situ, namely temperature, salinity and pH. The results showed that the type of substratewas muddy sand and organic mattersare classified as low. Suspended solids have not exceeded sea water quality standards. Water quality parameters were still supported for the life of aquatic organisms. The abundance of M. meretrix population was low, which was1.38 ind/m2. The distribution pattern was random and uniform which is dominated by classes measuring 54.6-63.6 mm from 6 size classes.Keywords: Meretrix meretrix, Abundance, Distribution, Size.